Entrepreneurship Teaching Culture and Entrepreneurship Education Factors : A Literature Review - Khiong, Khie (Journal of Industrial Engineering & Management Research, 2022)
The purpose of this study was to analyze the entrepreneurship teaching culture and entrepreneurship education factors. The research method is a literature review. The literature search in this literature review uses a database in the form of Google Scholar, Biomed Central, NCBI, and Proquest. After the articles were collected, the researchers grouped a number of articles that had been obtained based on the relevance of the topic of entrepreneurship. The articles that are prioritized revolve around the last 5 years of research, but if there is knowledge or discussion that has not changed, it will be expanded to become articles with the last 10 years of research. Critical appraisal is a journal analysis process that is used as a theoretical basis regarding the differences, similarities and shortcomings of the journals used. Journals are reviewed to select journals of measurement results that are appropriate to the topic. From searches that have been done on Google schoolar from 2019 to 2022 that meet the research topic. The data used in this study is secondary data which means not from direct observation, but obtained from the results of research that has been carried out by previous researchers. Sources of secondary data obtained in the form of journal articles about research variables. Education is a central issue in all sectors of life, not only is education merely the transfer of knowledge in schools, but education and teaching has a broad meaning, and we can learn from nature and the environment. A culture full of education will indirectly shape a society to coexist side by side. Teaching culture, with various ethical character values ​​reflected in the activities of daily life, entrepreneurship is no exception. Competence and entrepreneurial knowledge have been passed down from generation to generation by families and communities, so entrepreneurial values ​​have become part of the culture itself, including courage, self-confidence, interpersonal communication skills, discipline, hard work, high social and obedient for religion .